Public Expressions of Religion among Yogyakarta’s Salafi Muslimah - Marhumah, Marhumah; Muyyassaroh, Iffah Khoiriyatul; Sciortino, Rosalia (KARSA Journal of Social and Islamic Culture, 2024)
This study examines the manifestation of righteousness in public spaces among Salafi Muslim female students participating in Islamic study groups at four major universities in Yogyakarta, Indonesia. Using a qualitative case study approach, data were collected through six months of participant observation and in-depth interviews with eight key informants. The research explores how Salafi Muslim women internalize, negotiate, and practice hadith teachings daily, particularly in public settings. The findings reveal that these study groups significantly shape individual and collective expressions of piety. Participants exhibit varied approaches to negotiating religious teachings, with some finding clarity and structure, while others experience ambiguities, creating space for personal interpretation. This variation underscores the complex relationship between religious texts and individual agency, aligning with theoretical perspectives on spiritual practice. Additionally, the study highlights the importance of these groups in reinforcing social identities and facilitating engagement in public spaces. The research contributes to broader discussions on religious agency and public piety, providing insights into how Salafi Muslim women navigate the intersection of spiritual devotion and modern public life. Limitations include the focus on a specific group and reliance on self-reported data. Future studies should explore how piety is expressed across social and cultural contexts to deepen understanding of its role in public participation.